Acquisition of proviral DNA of mouse mammary tumor virus in thymic leukemia cells from GR mice. - Michalides, R (1982)
Male mice of strain GR develop T-cell leukemia at a low frequency late in life. These leukemia cells contain large amounts of mouse mammary tumor virus (MMTV) RNA and MMTV proteins in a precursor form (Nusse et al., J. Virol. 32:251-258, 1979). We used restriction enzyme analysis and molecular hybridization to identify MMTV proviruses in the DNA of these leukemia cells. GR leukemia cells contained additional integrated MMTV proviruses at various sites in the genome. This amplification of MMTV proviruses in GR leukemia cells is not restricted to one particular endogenous MMTV provirus of strain GR. The number and location of the extra MMTV proviruses present in transplants of GR leukemia cells did not change upon serial transplantation of the leukemia cells. Acquisition of MMTV proviruses was also found in a similar leukemia, L1210 of the DBA/2 mouse strain, but not in three other leukemias, SL2 of DBA/2, BW5147 of AKR, and a spontaneous thymoma of BALB/c. The two main classes of MMTV RNA, 35S and 24S, were present in the cytoplasmic RNA of GR leukemia cells, indicating that the aberrant processing of MMTV precursor proteins is not due to anomolously sized RNAs. We could not detect extra RNAs in GR leukemia cells which would represent read-through transcripts of cellular genes adjacent to the extra MMTV proviruses, initiated by a promoter signal in the right MMTV long terminal repeat sequence. These data suggest that acquisition of MMTV proviruses may coincide with the onset of leukemogenesis in GR male mice.